2009
DOI: 10.1021/jp9069042
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Study of the Monomeric Red Fluorescent Protein DsRed.M1

Abstract: We report a combined quantum mechanical/molecular mechanical (QM/MM) study of the DsRed.M1 protein using as QM component the self-consistent charge density functional tight-binding (SCC-DFTB) method in molecular dynamics (MD) simulations and hybrid density functional theory (DFT, B3LYP functional) in QM/MM geometry optimizations. We consider different variants of the chromophore (including the cis- and trans-acylimine and peptide forms) as well as different protonation states of environmental residues. The QM/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(67 citation statements)
references
References 77 publications
10
55
2
Order By: Relevance
“…The simulation system consisted of 23,641 atoms (TXS: 6133; cation: 53; PPi: 9; Mg 2+ : 3; Na + : 10; water: 17,433). The chosen MD setup is analogous to that of previous studies reported in the literature …”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation system consisted of 23,641 atoms (TXS: 6133; cation: 53; PPi: 9; Mg 2+ : 3; Na + : 10; water: 17,433). The chosen MD setup is analogous to that of previous studies reported in the literature …”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…The chosen MD setup is analogous to that of previous studies reported in the literature. [32,33,41,45] Three MD simulations with different initial velocity distributions (referred to as MD1, MD2, and MD3) were performed for each complex to enhance sampling. [30][31][32][33][34][35] All MD simulations were done with the CHARMM software package (version 35b2).…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…Proteins (2 mg/ml) were incubated in 15 µl gel filtration buffer, acidic buffer (0.1 M HCl) and alkaline buffer (0.1 M NaOH) for 10 min at room temperature [36]. Samples were incubated at 95°C for 10 min before loading on a 12% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent hybrid quantum/classical (QM/MM) studies on, for example, DsRed.M1 [36], [37] and HcRed [23], [38] provide detailed insights into the protonation states of the chromophore and surrounding residues, as well as the spectrosopic properties of these red fluorescent proteins. Together, these studies highlight the potential of computational approaches to elucidate the molecular mechanism that contribute to spectral properties of fluorescent proteins and that are not always obvious from crystallographic and spectral analysis alone.…”
Section: Introductionmentioning
confidence: 99%
“…38 Our groups have previously studied the structural and energetic properties as well as the absorption spectra of some RFPs (DsRed.M1 and HcRed). [39][40][41][42] In recent years, there has been much progress in theoretical research on electronically excited states, with MS-CASPT2 (multi-state complete-active-space second-order perturbation theory) 43,44 and coupled cluster methods (CC2, CCSD, CC3) [45][46][47] being well established for small molecules. Moreover, time-dependent density functional theory (TD-DFT) 48 has become popular for calculations on medium-sized molecules, giving reasonable results for various (but not all) types of excited states at relatively low computational cost.…”
Section: Introductionmentioning
confidence: 99%